Measurement of neutron dose component in central axis absorbed dose of 18 MV photon beam by TLD600 and TLD700 dosimeters - Hoda Darestani (Basic & Clinical Cancer Research, 2012)
Background: In spite of clinically useful photon and electron beams, high energy linacs produce secondary particles such as neutrons (photo-neutron production). Neutrons have important roles during treatment with high energy photons in terms of protection and dose escalation. In this project, neutron dose equivalent of 18 MV Varian accelerators is calculated by TLD600 and TLD700. Materials and Methods: For neutron and photon dose discrimination, first TLDs were calibrated versus definite gamma and neutron doses. Gamma calibration was done in two procedures; by standard 60Co source and by accelerator 18 MV photon beam. For neutron calibration by 241Am-Be source, irradiations were done in several different time intervals. Neutron dose equivalent was calculated in the central axis, on the phantom surface and depths of 1, 2, 3.3, 4, 5 and 6 cm. Results: No photo-neutron dose was achieved on the phantom surface and depths of 1, 2, 3.3 cm. The maximum photo-neutron dose equivalent was 50 mSv*Gy-1 at the depth of 5 cm. Conclusions: Photon absorbed dose calculation in central axis has an error of 5%. Neutron dose variation in different depths doesn’t show a regular procedure and in it seems to be due to the TLD inaccuracy for neutron dosimetry.